Study on frequency tracking method of ultrasonic scalpel based on impedance matching - Yang Lin; Dai Jianfeng; Zhao Hucheng; Gao Zhan; Lu Yang; Sun Xueming (Dianzi Jishu Yingyong, 2019)
With the development of science and technology, ultrasonic scalpel is widely used in medical treatment. In practical application, in order to make the transducer of the ultrasonic scalpel convert electrical energy into mechanical energy as much as possible, this paper uses parallel impedance matching to realize the impedance matching of the ultrasonic scalpel, which makes the transducer of the ultrasonic scalpel present pure impedance, thus maximizing the output power of the transducer and reducing the transmission of the transducer. Heat has increased the service life. In addition, the parameters of the transducer of the ultrasonic scalpel will change with temperature and environment in the course of using. Therefore, this paper designs a frequency tracking method for the resonant frequency of the transducer, which tracks the phase difference between current and voltage, and then sends it to the FPGA for calculation. A phase difference is obtained. When the phase deviation occurs, a frequency conversion formula is used to adjust the output frequency, so as to achieve the effect of frequency tracking. Through practical verification, the impedance matching and frequency tracking method of the ultrasonic scalpel designed in this paper can achieve the automatic frequency tracking under different loads, and run reliably.